Forward or backward inclination of the body and exertion of push or pull strength - Taniguchi, K.; Kubota, H.; Iteya, M. (Association for the Scientific Studies on Judo, Kodokan, 2023)
Objective: lt is well known in judo that a player becomes immobile when he/she is leaning. The purpose of this study was to clarify the relationship between the inclination of the body and strength exertions.